If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 3a = 17 + -1a Solving 15 + 3a = 17 + -1a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'a' to each side of the equation. 15 + 3a + a = 17 + -1a + a Combine like terms: 3a + a = 4a 15 + 4a = 17 + -1a + a Combine like terms: -1a + a = 0 15 + 4a = 17 + 0 15 + 4a = 17 Add '-15' to each side of the equation. 15 + -15 + 4a = 17 + -15 Combine like terms: 15 + -15 = 0 0 + 4a = 17 + -15 4a = 17 + -15 Combine like terms: 17 + -15 = 2 4a = 2 Divide each side by '4'. a = 0.5 Simplifying a = 0.5
| 0=-35m^2-17m-2 | | 9a-7=3a+11 | | y/5+2/7=y/7-2/7 | | 13x^2+4x+2x^2-3x= | | A=B-C-D-(E*A) | | 4(3+2h)-2(5+3h)= | | 5a-7=a+3 | | MS=WH-ST-SH-(I*MS) | | 8a+6=3a-9 | | 16=-3(2z-2)+2(z-4) | | 3a-2=2a+8 | | (4x^2-3x^3)-(9x^2-5x^3)=-5x^2-8x^3 | | 20x-5=0 | | 16x=49 | | 11x+14=5x+164 | | v=4/3(3.14)(3)^3 | | 0.28571428571(4m-18)=12 | | 3x-2(0)=-12 | | 65-5x=13x+19 | | 7(x-4)=5x-20 | | 10-8x=85-29x | | 4(x+9)=5-(3x-11) | | 7+2(5x-5)=9-4(2x+1) | | 3(0)-2y=-12 | | -x-6=3x-2 | | x=3x^2-x-4 | | 16x-6=10x | | 8+6(x+5)=4x-(3x+9) | | 9y(5)-2(2+7-18)= | | x=x^2-10x-11 | | 5y=12x-8 | | 20x+14y=3748 |